(untitled) (Ocean and Coastal Research, 2024)
Sponge-ophiuroid ecological associations, which are important in the dynamics of marine populations and communities, have been recorded for a long time. In this study, we report new records of interactions between sponges and ophiuroids, which were obtained by analyzing biological collections, to increase knowledge about the associations between these animals. The study observed 14 interactions between sponges and ophiuroids, eight of which are new to science: Ophiocnida scabriuscula and Agelas sp., Ophiothrix sp. and Monanchora arbuscula, Ophiactis quinqueradia and M. arbuscula, O. quinqueradia and Callyspongia ( Cladochalina) aculeata, Ophiactis savignyi and Agelas dispar, O. savignyi and M. arbuscula, O. savignyi and Topsentia ophiraphidites, and O. savignyi and Dysidea etheria. The specimens found were collected in four areas of the northeastern Brazilian coast (tropical southwestern Atlantic), including a conservation area and a mesophotic coral ecosystem. Thus, the continuation of studies and the implementation of conservation strategies for these environments are essential. Finally, the importance of biological collections as a crucial data source for biodiversity studies is reinforced.